Pemilihan dan Perawatan Baling-Baling Penggerak Perahu Nelayan Kec. Maros Baru - ., Baharuddin; Muhammad, A. Haris; Nikmatullah, Muh. Iqbal; Sitepu, Andi Husni; Rivai, Hariyanti; Shintarahayu, Balqis; Klara, Syerly; ., Zulkifly; Alwi, Rusydi; Hariyanto, Surya (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
The ship's driving system and propeller are components of the ship's propulsion device, and although they have been made in such a way and are strong, they will be damaged along with their service life. Damage to the propeller blades due to cavitation will have an impact, triggering noise and vibrations, and it will be the leading cause of decreased propeller thrust. Low ship propulsion efficiency increases fuel costs, making the ship unseaworthy and less efficient. Broken propeller blades when the ship is at sea threaten the safety of the ship and threaten the safety of the fishermen's lives. From the above conditions, the 2024 LBE-Collaboration PPM Program was held to provide counseling to members of the target fishermen group, "Kanja'tongeng", Borikamase Village, Maros Baru District, so that they can carry out maintenance on the ship's shaft and propeller independently in a good and correct manner. The evaluation results of activity achievements were carried out using the questionnaire method during the pre-test and post-test. Both showed a fairly adequate level of success. The number of participants who initially did not understand the extension material decreased from 67.86% to 12.05%. Likewise, there was an increased understanding of the material on ship shaft and propeller maintenance, as seen from the number of participants who initially understood it to an excellent level, from 11.90% to 39.16%. The achievement indicators above show that the PPM LBE-Collaboration 2024 program has been successful and is running effectively. This success, of course, not only increases the technical knowledge of fishermen about ship shaft and propeller maintenance, but will also improve aspects of ship safety and ship seaworthiness.